Eksplorasi Tantangan BPK Terkait Audit SDGs: Studi Kasus BPK Perwakilan Provinsi Sumatera Barat - Gita Gusriantika; Deviani Deviani (Universitas Negeri Padang, 2024)
This research aims to find out how the highest audit institution in West Sumatera (BPK) applies various strategies to audit SDGs implementation and the challenges they face (Case Study of BPK Representative of West Sumatra Province). This research is research with a qualitative approach using phenomenological research. This research looks at and listens more closely and in detail to individual explanations and understanding of their experiences and explores meaning through exploring the experiences of the subjects studied. Researchers in this study collected data through interviews with BPK auditors for West Sumatra Province. The results of the research state that BPK auditors have understood the potential challenges that exist, but have not been able to maximize SDGs audit performance, especially in the field of poverty. There is still little research regarding SDGs Audit Challenges carried out by BPK auditors. And researchers conducted research in the West Sumatra Province area, where in this area the research carried out by researchers was something new. This research has a contribution, namely that based on the research results, it can pay attention to strategies in auditing the implementation of SDGs, especially in the field of poverty, and can be an inspiration for anyone to carry out similar research.